Adjuvant effects of Saccharomyces cerevisiae in the treatment of experimental periodontitis in rats undergoing chemotherapy - Valdir Gouveia GARCIA; Tiago Esgalha da ROCHA; Natália Amanda GOMES; Daniela Maria Janjácomo MIESSI; Marta Aparecida Alberton NUERNBERG; João Victor Soares RODRIGUES; Jânderson de Medeiros CARDOSO; Edilson ERVOLINO; Letícia Helena THEODORO (University of São Paulo, 2023)
Abstract Surgical procedures, radiotherapy, and chemotherapy, individually or in association, are current oncological treatments. Among the most used chemotherapy drugs, 5-fluorouracil (5FU) is an antimetabolite with a broad spectrum of action. This study evaluated the effects of probiotics (PRO) as an adjuvant to the treatment of experimental periodontitis (EP) in rats immunosuppressed with 5FU. Methodology 108 rats were randomly allocated to six different groups: EP; SS - systemic treatment with saline solution (SS); 5FU - systemic treatment with 5FU; 5FU+PRO - systemic treatment with 5FU, followed by the local administration of Saccharomyces cerevisiae ; 5FU+SRP - systemic treatment with 5-FU, followed by scaling and root planing (SRP); and 5FU+SRP+PRO - systemic treatment with 5FU followed by local treatments with SRP and PRO. Immunosuppression was obtained at two points: at the time of ligature installation and after 48 h. Six animals from each group were euthanized at seven, 15, and 30 d and hemimandibles were collected and processed for histopathological, histometric, and immunohistochemical analysis. Data were subjected to statistical analysis (α=5%). Results At 7 d, the 5FU+PRO group showed less bone resorption and better structured connective tissue compared with the EP, SS, 5FU+SRP, and 5FU+SRP+PRO groups. At 15 d, the 5FU+SRP group showed a greater intensity of the inflammatory response (p<0.05). At 30 d, the 5FU+SRP+PRO group showed better structured bone tissue and a higher percentage of bone tissue (PBT) than the EP, SS, 5FU, and 5FU+PRO groups (p<0.05). Conclusion The use of Saccharomyces cerevisiae as monotherapy or as an adjuvant to periodontal therapy may have a positive effect on bone repair in immunosuppressed conditions.